Hubungan Paritas Dan Usia Ibu Hamil Dengan Kejadian Hipertensi Pada Kehamilan Di Puskesmas Bojongsari Kabupaten Purbalingga Tahun 2022 - Mulyani, Anisa Tri; Haniyah, Siti; Yanti, Linda (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hypertension poses a global health challenge and significantly increases the risk of cardiovascular diseases, stroke, kidney problems, and other related conditions. The objective of this research is to investigate the relationship between parity and the age of pregnant mothers with the occurrence of hypertension at the Bojongsari Community Health Center in Purbalingga Regency in the year 2022. The research method employed a retrospective approach with total sampling. The results of the statistical tests indicate no significant relationship between parity and the age of pregnant mothers with the occurrence of hypertension at the Bojongsari Community Health Center in Purbalingga Regency in 2022, with non-significant p-values (p > 0.05) for parity (p-value = 0.142) and age variable (p-value = 0.832). In conclusion, there is no significant relationship between parity and the age of pregnant mothers with the occurrence of hypertension during pregnancy at the Bojongsari Community Health Center in Purbalingga Regency in 2022. It is recommended that healthcare professionals, especially midwives, provide health education on hypertension during pregnancy and ensure regular antenatal care examinations to detect potential complications early in both the mother and the fetus.